Educação escolar quilombola: a matemática presente em materiais publicados no site do Ministério da Educação - Crestani, Maiéli Masteloto (2020)
The main objective of this research was to analyze if and how the mathematical content is approached in the materials published, available in the platform of the educational modality Quilombola School Education (QSE), on the Ministry of Education's website. Thus, with the purpose of knowing more about the theme, mappings were made in two different places: Catálogo de Teses e Dissertações da CAPES and Google Scholar. The papers found were categorized, and only those that fell into the following categories were selected for a thorough reading, as they presented greater approximations and contributions to the development of this dissertation, they are: analysis of materials directed to QSE and Mathematics focused on QSE. With this same purpose, we also carried out a research on official documents and authorial works that approached historical issues, thus constituting a brief historical overview of the education offered to the Afro-Brazilian population and, specifically, to the quilombola population until we got to the current context. In relation to the theoretical contributions used, these are directly related to education in different contexts, more specifically about the teaching and learning of mathematics in quilombola communities, as well as about the didactic materials and pedagogical support directed to the QSE educational modality. The research has a qualitative approach, being defined as bibliographic according to its procedures and having Bardin's Content Analysis (2016) as a method of data analysis. The categories for data analysis, selected from what was obtained in the materials published on the MEC website, were established considering the themes that the math content is related, which are: Sports/Games/Play; Teacher Training; Art; Parties/Religion; Food Production/Storage/Collection/Commercialization; Environmental Problems; Women; Circularity; Health; Population Characteristics; Education; Labor Market; Quilombola History and Organization. After the analysis of the materials and the discussions concerning them, we make considerations concerning the development of the dissertation as a whole and specific issues concerning the analyses. About them, the topics that we considered most relevant were: the emphasis given to the materials, the contributions of the African and Afro-Brazilian population to the constitution of Brazilian society, and the issue of mathematics presented in most of them being directly related to cultural aspects of the communities.